2017
DOI: 10.1097/acm.0000000000001565
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Performance Evaluations of Third-Year Medical Students and Association With Student and Evaluator Gender

Abstract: A one-year examination of all third-year clerkship clinical performance evaluations at a single institution revealed that male and female evaluators rated male and female students differently, even when accounting for other measured variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 26 publications
0
34
1
Order By: Relevance
“…Conversely, evaluation of clinical performance of final‐year students on core equine and small animal rotations suggested that male students performed slightly better. This observation contrasts with findings in medical education, where no gender effect was observed or where female clinical performance was higher . This may reflect a gender bias based on smaller numbers of male students in veterinary cohorts or may be indicative of inherent difficulties with assessing clinical performance.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Conversely, evaluation of clinical performance of final‐year students on core equine and small animal rotations suggested that male students performed slightly better. This observation contrasts with findings in medical education, where no gender effect was observed or where female clinical performance was higher . This may reflect a gender bias based on smaller numbers of male students in veterinary cohorts or may be indicative of inherent difficulties with assessing clinical performance.…”
Section: Discussioncontrasting
confidence: 91%
“…This observation contrasts with findings in medical education, where no gender effect was observed or where female clinical performance was higher. 23,24 This may reflect a gender bias based on smaller numbers of male students in veterinary cohorts or may be indicative of inherent difficulties with assessing clinical performance. In the current study, data from only the two compulsory internal (on campus) rotations were included, as rotations at different distributed practices or based on different elective choices were considered to possibly introduce greater heterogeneity into the data analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to potential ethnic-related bias affecting student grades, the effect of gender on the clinical performance of students is also a major concern [50,51]. Female students are more likely to perform better on communication and interpersonal skills than males [52][53][54][55] as well as on the overall performance of both written tests and clinical skills [27,35,44,51,56]. Furthermore, studies reported that medical students who showed empathy received better clinical evaluations, with women receiving higher scores on empathy scales than men [57].…”
Section: Clinical Performance Of Students Based On Gendermentioning
confidence: 99%
“…In other words, this group of students followed the textbook guideline to communicate with patients that may be less demanding of communication skills and perceived as appropriate. Additionally, female students or physicians perform better in communication and interpersonal skills with patients [52][53][54]59,72,73], which could be correlated to their abilities to actively listen and a greater sense of patient care values, female practitioners may also nd it easier to build rapport with patients [74]. It seems that students from the ethnic majority and female students can do better in CPAs because of their greater communication or interpersonal skills.…”
Section: Predictors Of Underperformancementioning
confidence: 99%
“…16 Impressions of learner performance are influenced by unconscious biases, and differences in clerkship grades reported by students who are nonwhite, male, or reticent heighten concern about fairness. [18][19][20][21][22][23][24] These issues illustrate the complexity of information that must be considered when assigning clerkship grades.…”
Section: Introductionmentioning
confidence: 99%